Enhanced analysis of kippo-honeypot in cloud - Alzubaidi, Mohammed Abdullah Omar (2015)
Cloud computing is a promising technology for business and individuals. Cloud computing allows companies to focus more on their core business and leave the IT management responsibilities to cloud vendors. However, not many companies have considered shifting their business to the cloud due to security issues that cloud computing has. Nevertheless, many researchers have suggested methods to mitigate those attacks, some have proposed methods to extract the features of attacks and then use them to help in detecting future attacks. This project aims to support the existing attacks analysis methods to learn more about attack patterns and attackers’ behavior, which will contribute to building more reliable attack mitigation techniques and tools. The proposed system aims to enhance the analysis of honeypot data collected from attacks in cloud by implementing new data analysis tools that can extract more data from the honeypot database and correlate them to produce richer data analysis visualization, as compared to previous systems like Honeypots in the Cloud system. The analysis result is more attack informative and gives better understanding of attacks to the system administrator